Automatic Mango Detection Using Texture Analysis and Randomised Hough Transform - Mohd Fadzil, Abdul Kadir; Abd.Rasid, Mamat; Azrul Amri, Jamal (Hikari Ltd., 2015)
This paper presents a method of detecting overlapping mango fruits from the complex background image. This research uses image that is obtained from a digital camera. This method is based on pre-processing the input image using the texture analysis to determine the boundary of each overlapping fruits. The image is processed to determine the actual boundary, converted to binary images, and utilise dilation and erosion to determine the object. We use ellipse fitting by applying Randomized Hough Transform to search the potential area of the mango fruit. Ellipse fitting are chosen because the shape of the mango fruit is similar to ellipse shape. Using these techniques, the fruit is successfully detected including the fruits that are overlapping with each other.